ISOLATION AND BIOCHEMICAL CHARACTERIZATION OF RHIZOBIUM MELILOTI FROM ROOT NODULES OF ALFALFA ( MEDICO SATIVA) - F. Shahzad; M. Shafee; F. Abbas; S. Babar; M. M. Tariq; Z. Ahmad (Journal of Animal and Plant Sciences, 2012)
The Rhizobium a nitrogen fixing bacteria is the essential feature of leguminous plants. Increased cultivation of legumes is essential for the regeneration of nutrient-deficient soils and providing needed nutrients to humans and animals. The present study was aimed to isolate the beneficial nitrogen fixing rhizobium from root nodules of Alfalfa (Medico sativa) plant. Total of Fifty (50) nodules samples were collected equally from five different localities of District Quetta Balochistan, Pakistan and were subjected to culture on differential media Bromothymol Blue (BTB) added Yeast Extract Mannitol (YEM). After series of biochemical and Sugar Fermentation tests twenty Five (25) samples were identified as Sinorhizobium meliloti. The organism was present in all areas. This study confirms the presence of Rhizobia in leguminous fodder in the area.
Keywords: Root nodules; alfalfa; Rhizobium meliloti; bromothymol blue